1994
DOI: 10.1159/000462557
|View full text |Cite
|
Sign up to set email alerts
|

A New Low-Frequency Red Cell Antigen, 'SARAH'

Abstract: There are more than 100 low-frequency antigens (LFAs) which have been given International Society of Blood Transfusion (ISBT) numbers as members of systems, collections or the 700 series. In addition, there are a number of well-known (to reference laboratories) unpublished LFAs. The presence of an LFA was suspected when 2 sera were found to react with a single example of K homozygous cells. Anti-K reacting with K homozygotes was eliminated on testing with other KK cells. Testing of the reactive cell with antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…At first sight, these findings are in contrast with the original publication, which suggested that SARA was not an MNS blood group antigen as the SARA antigen is resistant to ficin and papain treatment while many MNS antigens, including M, N, Vw, Hut, Mur, M g , Vr, Hop, Bun, Mut, and Os a , are sensitive to treatment by these enzymes . However, this can be explained as on the glycophorin A molecule, Gly78 is a ficin proteolytic site and Arg80 is a papain proteolytic site.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…At first sight, these findings are in contrast with the original publication, which suggested that SARA was not an MNS blood group antigen as the SARA antigen is resistant to ficin and papain treatment while many MNS antigens, including M, N, Vw, Hut, Mur, M g , Vr, Hop, Bun, Mut, and Os a , are sensitive to treatment by these enzymes . However, this can be explained as on the glycophorin A molecule, Gly78 is a ficin proteolytic site and Arg80 is a papain proteolytic site.…”
Section: Discussionmentioning
confidence: 59%
“…* a Individuals who were participants in this current study; b individuals who were deceased before commencement of this study and whose serologic profiles were obtained from the original SARA study, noting that Individual I‐1 was deceased before discovery of the SARA antigen…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two antigens have been added to the MNS system. Exome sequence analysis of samples from SARA+ and SARA– family members identified a single nucleotide change c.240G>T in exon 3 of GYPA , which changes p.Arg80Ser. Sequence analysis of unrelated SARA+ samples confirmed the causative polymorphism .…”
Section: New Blood Group Antigensmentioning
confidence: 99%
“…Low‐prevalence antigens that have not been assigned to a blood group system and that are recognized by the International Society for Blood Transfusion are included in the 700 series of antigens 1 . The SARAH (SARA) antigen was first detected in 1990 on the red blood cells (RBCs) of an Australian blood donor (SH) whose cells were used in an antibody identification panel 2 . A serologic investigation was initiated when a patient's serum reacted only with this donor's RBCs.…”
mentioning
confidence: 99%